A sliding mode control strategy for a grid-supporting and grid-forming power converter in autonomous AC microgrids - Khongkhachat, S.; Khomfoi, S. (My University, 2019)
– This paper presents a sliding mode control technique combined with voltage orientation for grid-supporting and grid-forming (GSGFm) function in a power converter, used in AC microgrid during island operation. The robustness sliding mode control method (SMC) can provide stability control system and fast dynamic response. Therefore, a control law is designed using sliding mode techniques, which is based on the combination of continuous and discrete signals to generate the robustness system from uncertainties and disturbances. A sliding mode control approach is adopted in this paper in order to enhance for the inner control loops (level 0) to improve the dynamic response of a lowest hierarchical level based on droop regulated-microgrids. The main objectives of the proposed SMC technique are to keep frequency and voltages at normal values, according to the actual real-reactive power loads absorption. SMC has also produced the reference frequency and the voltage signals. Thereupon, the dynamic frequency and voltage can be regulated with a new control approach and can guarantee power reliability, quality and efficiency during this mode. Finally, the model and the controller design are validated by simulation and experimental results. The results show that the proposed SMC technique can be implemented in a GSGFm power converter for AC microgrid.
Keywords: Autonomous AC Microgrids; Grid-Supporting and Grid-Forming (GSGFm); Power Converter; Sliding Mode Control (SMC); Voltage-Oriented Control